Bacterial Population and Chemical Characteristics of Fermented Mandai Cempedak with Starter Induction (Indonesian Society for microbiology, 2018)
Traditionally fermented foods can be improved by introducing starter and hygienic production. The study observes the changes in population of lactic acid bacteria (LAB), pH, polyphenolic levels, and antioxidant activity of spontaneous and L. casei induced mandai cempedak fermentation at 37 °C for seven days. The hygienic process included two steps boiling of inner skin of cempedak at 80-90 °C for 15 minutes. LAB and non-LAB growth were quantified with plate count. Phenolic substances were spectrophotometrically quantified. Gallic acid (GAE), tannic acid (TAE), and catechin (CE) were used as standards. DPPH method was employed to measure antioxidant activity. LAB dominated bacteria population during the course of fermentation. The LAB grew from 3,3±0,5 to 8,8±0,6 log cfu/ml for spontaneous fermentation and from 3,3±0,4 to 9,0±0,5 log cfu/mL for starter induced fermentation. The population of BAL in spontaneous and L. casei induced fermentation grew in almost similar fashion and can be approached by linear regression. The degree of acidity increased during the course of fermentation and achieving pH 3,5 at the sixth day of fermentation. Fermentation increased the phenolic contents both in spontaneous and L. casei induced fermentation, and resulting in enhancing the antioxidant activity. The phenolic contents, except total tannins, were higher in starter induced fermentation, thus lowering IC50 inhibitions of DPPH reduction. Hence, L. casei produced fermented products with better antioxidant activity in comparison to spontaneously fermented products. From these parameters, L. casei was successfully used as starter for mandai cempedak and optimum fermentation at 37 °C was 6 days.